Loser Nanotechnology - Still Waiting for Nanotube Memory Chip. - Ross, P.E (IEEE spectrum)
Nantero's alternative to flash memory has reached its sell-by date. Nantero's technology, based on carbon nanotubes, seemed to be the opening salvo in the nano-technology revolution. Nanotechnology nanotube-based nonvolatile memory chip is developed.